Effects of meal and incretins in the regulation of splanchnic blood flow - Koffert J; Honka H; Teuho J; Kauhanen S; Hurme S; Parkkola R; Oikonen V; Mari A; Lindqvist A; Wierup N; Groop L; Nuutila P (BIOSCIENTIFICA LTD, 2022)
Objective: Meal ingestion is followed by a redistribution of blood flow (BF) within the splanchnic region contributing to nutrient absorption, insulin secretion and glucose disposal, but factors regulating this phenomenon in humans are poorly known. The aim of the present study was to evaluate the organ-specific changes in BF during a mixed-meal and incretin infusions.Design: A non-randomized intervention study of 10 healthy adults to study splanchnic BF regulation was performed.Methods: Effects of glucose-dependent insulinotrophic polypeptide (GIP) and glucagon-like peptide 1 (GLP-1) infusions and mixed-meal were tested in 10 healthy, glucose tolerant subjects using PET-MRI multimodal imaging technology. Intestinal and pancreatic BF and blood volume (BV) were measured with O-15-water and O-15-carbon monoxide, respectively.Results: Ingestion of a mixed-meal led to an increase in pancreatic and jejunal BF, whereas duodenal BF was unchanged. Infusion of GIP and GLP-1 reduced BF in the pancreas. However, GIP infusion doubled blood flow in the jejunum with no effect of GLP-1.Conclusion: Together, our data suggest that meal ingestion leads to increases in pancreatic BF accompanied by a GIP-mediated increase in jejunal but not duodenal blood flow.